A atuação dos provedores de serviços de internet no controle de conteúdos postados por terceiros e a necessidade de intervenção judicial - Souza, Carmen Lilian Oliveira de (2024)
This study will analyze the legal and juridical aspects related to the civil liability of internet service providers with regard to content posted by third parties. Aspects brought in by the Marco Civil da Internet Law will be highlighted, precisely those related to the need for judicial intervention in the removal of posts. Details about the emergence of the internet and its regulatory evolution, with the presentation of some concepts specific to the virtual world, will also be analyzed, both in the context of Brazilian law and comparative law. This is because the increase and speed with which information is disseminated in the virtual environment has brought a mixture of satisfaction and concern to individuals, as fundamental rights and principles related to communicative freedoms have come to be confronted with those guaranteeing individual freedoms. In the course of this research, it became clear that it is not plausible for application providers to depend on a court order to remove harmful content, and that they should therefore remove the post as soon as they become aware of the unlawful content, or even when they are notified by the user or the victim, so as to leave only complex demands to the Judiciary. To develop the work, the hypothetical-deductive method was used, with qualitative research of documentary and legislative analysis, national and foreign, as well as a more up-to-date bibliographic review on the subject under study, with judgments from the Federal Supreme Court, the European Union and the United States, which touched on this discussion.